The strong women of Modhupur - Burling, Robbins (Dhaka : University Press, 1997)
On Garo, Indic people of Madhupur, Bangladesh.
Includes bibliographical references (pages [267]-268) and index.
BIED
Keywords: Garo (Indic people) -- Bangladesh -- Madhupur; Madhupur (Bangladesh) -- History